Efektivitas Metode Pembelajaran Sorogan dalam Meningkatkan Prestasi Hasil Belajar Santri Kelas Sifir Robi’ (A) pada Mata Pelajaran BMK (Bimbingan Membaca Kitab) di Madrasah Diniyah Pondok Pesantren Qomaruddin Sampurnan Bungah Gresik - Moh. Syafi’i; Muhammad Nasta’in; M. Nawawi (Jurnal Keislaman, 2023)
The BMK (Book Reading Guidance) lesson is one of the lessons taught at the Qomarudin Sampurnan Bungah Gresik Madrasah Diniyah Islamic Boarding School which is given to students of the Tsalis magic class, Robi. Khomis, and Sadist. The salaf book used is the book of Fathul Qorib. The BMK learning method at Madrasah Diniyah Qomaruddin so far has been bandongan (lectures). The sorogan method is a learning activity for santri that focuses more on developing individual abilities under the guidance of a kyai/ustadz. The purpose of implementing the sorogan method is to improve the ability of the students personally so as to produce a more stable learning achievement for each student. The method in this research is classroom action research with a qualitative approach. The subjects of the study were 24 students of the Madrasah Diniyah Pondok Pesantren Qomaruddin Sampurnan Bungah. Data collection procedures carried out by means of observation, interviews and documentation. The results showed that the effectiveness of the sorogan method was quite good. The classical values ​​before cycle, cycle I, and II were respectively 25%, 66.67% and 100%. The average value of students increased in each cycle from 67.17, 68.75 and in cycle II to 89.79. The results of this study indicate that the sorogan method is classified as effective in increasing BMK (Book Reading Guidance) learning achievement for students.